Mental health in the COVID-19 pandemic: A longitudinal analysis of the CLoCk cohort study. - Laura Panagi; Simon R White; Snehal M Pinto Pereira; Manjula D Nugawela; Isobel Heyman; Kishan Sharma; Terence Stephenson; Trudie Chalder; Natalia K Rojas; Emma Dalrymple; Kelsey McOwat; Ruth Simmons; et al. (PLoS Medicine)
Background Little is known about the long-term mental health consequences of the pandemic in children and young people (CYP), despite extremely high levels of exposure to the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus and the disruption to schooling and leisure activities due to the resultant restrictions. There are mixed findings from systematic reviews of how the pandemic affected CYP's mental health, which may be due to heterogeneous methods and poor quality studies. Most, but not all, suggest deterioration in mental health but population level studies may obscure the differing experiences of subgroups. The study questions are: (i) are there subgroups of CYP with distinct mental health profiles over the course of the second year of the Coronavirus Disease 2019 (COVID-19) pandemic (between April 2021 and May 2022); and (ii) do vulnerability factors influence CYP's mental health trajectories. Methods and findings A matched longitudinal cohort study of non-hospitalised test-positive and test-negative 11- to 17-year-old CYP in England were recruited from the UK Health Security Agency having undergone PCR testing for COVID-19. They completed the Strengths and Difficulties Questionnaire (SDQ) at least twice over a 12-month follow-up period. Overall, 8,518 of 17,918 (47.5%) CYP who returned their first SDQ at 3 or 6 months post-testing were included in the analytical sample. Associations between age, sex, ethnicity, socioeconomic status (SES), and an educational health and care plan (EHCP, indicating special educational needs) on SDQ score trajectories were examined separately, after adjusting for PCR test result. Findings from multilevel mixed-effects linear regression model showed that on average mental health symptoms as measured by the total SDQ score increased over time (B = 0.11 (per month), 95% CI = 0.09 to 0.12, p < 0.001) although this increase was small and not clinically significant. However, associations with time varied by age, such that older participants reported greater deterioration in mental health over time (B = 0.12 (per month), 95% CI = 0.10 to 0.14 for 15 to 17y; 0.08 (95% CI = 0.06 to 0.10) for 11 to 14y; pinteraction = 0.002) and by sex, with greater deterioration in girls. Children with an EHCP experienced less deterioration in their mental health compared to those without an EHCP. There was no evidence of differences in rate of change in total SDQ by ethnicity, SES, or physical health. Those with worse prior mental health did not appear to be disproportionately negatively affected over time. There are several limitations of the methodology including relatively low response rates in CLoCk and potential for recall bias. Conclusions Overall, there was a statistically but not clinically significant decline in mental health during the pandemic. Sex, age, and EHCP status were important vulnerability factors that were associated with the rate of mental health decline, whereas ethnicity, SES, and prior poor physical health were not. The research highlights individual factors that could identify groups of CYP vulnerable to worsening mental health.